The impact of Silica fertilizer on growth, biomass and nutrient absorption of potted seedlings of Persian oak - Mehrdad Zarafshar; Seyed Kazem Bordbar; Mohammad Matinizadeh; Alireza Abbasi; Mohammadreza Negahdarsaber; Shahram Ahmadi; Saied Bahrami; Hassan Rezaie (فیزیولوژی محیطی گیاهی, 2020)
The study of various affecting factors in order to promote seedling growth at nursery and afforestation areas is very important. Although silicon is not recognized as an essential element in plants, it has very beneficial effects on plant species. For this purpose, an experiment was conducted following a completely randomized design with 5 treatments to evaluate different concentrations of silica on some growth parameters and nutrient uptake in Iranian oak seedlings. For each treatment, 10 pots were considered and treatments were performed including control and irrigation treatments with concentrations of 50, 150, 350 and 500 mg L-1 silica (based on field capacity). The result showed that silica had no statistically significant effect on basic diameter but root volume and stem diameter in seedlings treated with 500 mg L-1 were greatre around more than 50% in comparison with control seedlings. On the other hand, seedlings treated with 500 mg L-1 silica had the highest dry biomass compared to control and other treatments so that the leaf, stem and root biomass of the treatment were higher around 68-80% than control seedlings. The highest absorption of nitrogen, potassium and calcium were observed in 150 mg L-1 treatment. However, at low concentrations, silica decreased the uptake of manganese, copper and zinc and decreased the amount of iron uptake in the presence of silicon. Finally, it can be concluded that the use of silica in this study increased the total biomass of oak seedlings and also increased the absorption of macro elements so, the finding can be considered in forest nursery to seedling production. Nevertheless, further studies are needed to understand its mechanism, including gene and protein expression analysis.